Simple method for culture of peripheral blood lymphocytes of Testudinidae. - Silva, T. L.; Silva, M. I.; Venancio, L. P.; Zago, C. E.; Moscheta, V. A.; Lima, A. V.; Vizotto, L. D.; Santos, J. R.; Bonini-Domingos, C. R.; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Genetics and Molecular Research, 2011)
We developed and optimized a simple, efficient and inexpensive method for in vitro culture of peripheral blood lymphocytes from the Brazilian tortoise Chelonoidis carbonaria (Testudinidae), testing various parameters, including culture medium, mitogen concentration, mitotic index, culture volume, incubation time, and mitotic arrest. Peripheral blood samples were obtained from the costal vein of four couples. The conditions that gave a good mitotic index were lymphocytes cultured at 37°C in minimum essential medium (7.5 mL), with phytohemagglutinin as a mitogen (0.375 mL), plus streptomycin/penicillin (0.1 mL), and an incubation period of 72 h. Mitotic arrest was induced by 2-h exposure to colchicine (0.1 mL), 70 h after establishing the culture. After mitotic arrest, the cells were hypotonized with 0.075 M KCl for 2 h and fixed with methanol/acetic acid (3:1). The non-banded mitotic chromosomes were visualized by Giemsa staining. The diploid chromosome number of C. carbonaria was found to be 52 in females and males, and sex chromosomes were not observed. We were able to culture peripheral blood lymphocytes of a Brazilian tortoise in vitro, for the preparation of mitotic chromosomes.
Keywords: colchicine; fixative; mitogenic agent; phytohemagglutinin; animal; Brazil; chemistry; chromosome; chromosome banding pattern; culture medium; culture technique; cytology; drug effect; female; genetics; Giemsa stain; human; lymphocyte; male; mitosis index; turtle; Animals; Azure Stains; Cell Culture Techniques; Chromosome Banding; Chromosomes; Colchicine; Culture Media; Female; Fixatives; Humans; Lymphocytes; Male; Mitogens; Mitotic Index; Phytohemagglutinins; Turtles